Semiotic Analysis of Oatside Video Advertisement “Enaknya Oatside Bikin Jadi Lupa Teman” - Nur Fadillah; Reski Nurhidayah; Muh. Hasbi (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
The objectives of this research are to find out what visual signs are contained in the Oatside brand beverage advertisement with the tagline “Enaknya OATSIDE Bikin Jadi Lupa Teman” and to understand how these visual signs convey the messages and information contained in the advertisement to the target market. The data of this research was obtained by watching the advertisement, tracing all the visual signs, and then identifying and collecting existing signs. Data analysis uses an interactive analysis model which includes data condensation, data display, and conclusion drawing. This research uses Roland Barthes’ semiotic categories consisting denotation, connotation, and myth to analyze the visual signs contained in the advertisement. The results of this study found 14 scenes of visual signs in Oatside advertisements that were interpreted to deliver messages and information to consumers well that the product has an extraordinary taste. Apart from that, the advertisement also has considerable potential to influence consumers through the use of humor, attractive visuals and relation, and create emotional connection with the audience.